Expression and structural analysis of human neuroligin 2 and neuroligin 3 implicated in autism spectrum disorders - Zhang, Zhenzhen; Hou, Mengzhuo; Ou, Huaxing; Wang, Daping; Li, Zhifang; Zhang, Huawei; Lu, Jianping (Frontiers in Endocrinology, 2022)
Development of autism spectrum disorders (ASD) involves in both environmental factors such as maternal diabetes and genetic factors such as neuroligins (NLGNs). NLGN2 and NLGN3 are two members of NLGNs with distinct distributions and functions in synapse development and plasticity. The relationship of maternal diabetes and NLGNs, and the distinct working mechanisms of different NLGNs currently remain unclear. Here, we firstly analyzed the expression levels of NLGN2 and NLGN3 in streptozotocin-induced ASD mouse model and in different brain regions to reveal their differences and similarities. Then, cryo-EM structures of human NLGN2 and NLGN3 were determined. The overall structures are similar as their homologs in previous report. However, structural comparisons revealed the relative rotations of two protomers in the homodimer of NLGN2 and NLGN3. Taken together with previously reported NLGN2-MDGA1 complex, we speculate that the distinct assembly adopted by NLGN2 and NLGN3 may affect their interactions with MDGAs. Our results provide structural insights into the potential distinct mechanisms of NLGN2 and NLGN3 implicated in the development of ASD.